Project-based learning: video game development as a tool to integrate ecology, genetics, evolution and informatics - Bernini, Maria A. M.; Carvalho, Adolfo L.; Carlos-Bender, Jaqueline (Revista Saúde & Diversidade, 2019)
Introduction: Active, student-centered learning encourages the development of 21st century skills and competences. Many of them encourage, in addition to autonomy, interdisciplinarity. Therefore, the participation of students in the creation and not only the stimulation of the use of technologies is extremely relevant. Considering the importance of multidisciplinarity that must envolve the learning process, new approaches such as Project Based-Learning have been developed, seeking greater involvement of the students in learning-related decisions. Objective: Aiming the interdisciplinarity that the integrated educational system requires, the purpose of this study was to analyze the development of games as an integration tool, between biology and computing area. The games have been developed along with the subjects of Entrepreneurship and Practical Projects III. Methods: Classes have been held so that high school students could grasp the contents of Evolution, Genetics and Ecology, which would be the central themes of the games. Results: Groups who have chosen Evolution to work with had greater difficulty in understanding the contente whereas those who have worked with Ecology and Genetics outdid the formers. The Game Maker program stood out being the most used tool for the game’s making process. Conclusion: The acceptance of the project by the students leads to the conclusion that innovative methodologies such as project-based learning is a great tool in education, so that the groups could be more involved in class and the subjects could be linked together.